(untitled) (Nóema, 2023)
This article starts from the analysis set out by Jean-François Lyotard in his famous 1979 text The Postmodern Condition, where he considers how, with the exhaustion of the grand narratives that legitimised the institutions of knowledge in the last two centuries, all the procedures of research and the transmission of knowledge have as their only guiding principle that of performance, now extended by the liberalist political economy to every sphere. The comparison with Nietzsche helps us to understand how such major narratives are already originally compromised with passions that innervate the institutions of mass knowledge and that the ideological apparatuses tend not to recognise and conceal. Recourse to Spinoza makes it possible to analyse the “affective life” of institutions, which necessarily draw their strength from a sort of affective drain, the only one capable of binding to them the multitude of men, most of whom are slaves to their passions. As far as education is concerned, Spinoza seems to suggest that it should not be entrusted only to governmental institutions that are also traversed by the passions, instead education of others should be made the task of every free man who - guided only by a rational desire - can only show all the ars and ingegno he possesses in such an undertaking.